Software application for solving game theory problems. (21st May 2021) - Hrustek, Nikolina Žajdela; Perši, Nenad; Kliček, Dino
Decision-making is a complex assignment, especially in situations of conflict. One way to deal with such problematic situations is game theory application. The purpose of this paper is to present the theoretical and practical application of game theory with emphasis on matrix games and linear programming application. The paper presents an overview of a developed software tool that simplifies solving problems for the user with help of simplex algorithm. Practical starting point on game theory efficiency is provided by demonstrating the application on a real problem.